Comparison of automated SARS-CoV-2 antigen test for COVID-19 infection with quantitative RT-PCR using 313 nasopharyngeal swabs, including from seven serially followed patients. (October 2020) - Hirotsu, Yosuke; Maejima, Makoto; Shibusawa, Masahiro; Nagakubo, Yuki; Hosaka, Kazuhiro; Amemiya, Kenji; Sueki, Hitomi; Hayakawa, Miyoko; Mochizuki, Hitoshi; Tsutsui, Toshiharu; Kakizaki, Yumiko; Miyashita, Yoshihiro; et al.
Highlights: We assess the performance of the LUMIPULSE antigen test compared to RT-qPCR The antigen level was significantly higher in PCR-positive samples than in negative samples The antigen test determined all samples (>100 viral copies) to be positive Likewise, it determined 85% of samples (>10 viral copies) to be positive The kinetics of viral loads and antigen levels showed a similar declining trend Abstract: In routine clinical practice, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is determined by reverse-transcription PCR (RT-PCR). In the current pandemic, a more rapid and high-throughput method is in growing demand. Here, we validated the performance of a new antigen test (LUMIPULSE) based on chemiluminescence enzyme immunoassay. A total of 313 nasopharyngeal swabs (82 serial samples from 7 infected patients and 231 individual samples from 4 infected patients and 215 uninfected individuals) were analyzed for SARS-CoV-2 with quantitative RT-PCR (RT-qPCR) and then subjected to LUMIPULSE. We determined the cutoff value for antigen detection using receiver operating characteristic curve analysis and compared the performance of the antigen test with that of RT-qPCR. We also compared the viral loads and antigen levels in serial samples from seven infected patients. Using RT-qPCR as the reference, the antigen test exhibited 55.2% sensitivity and 99.6% specificity, with a 91.4% overall agreement rate (286/313). In specimens with > 100 viral copies and between 10 and 100 copies, the antigen test showed 100% and 85% concordance with RT-qPCR, respectively. This concordance declined with lower viral loads. In the serially followed patients, the antigen levels showed a steady decline, along with viral clearance. This gradual decline was in contrast with the abrupt positive-to-negative and negative-to-positive status changes observed with RT-qPCR, particularly in the late phase of infection. In summary, the LUMIPULSE antigen test can rapidly identify SARS-CoV-2-infected individuals with moderate to high viral loads and may be helpful for monitoring viral clearance in hospitalized patients.